2021
DOI: 10.1101/2021.02.03.428245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDK4/6 inhibitors induce replication stress to cause long-term cell cycle withdrawal

Abstract: CDK4/6 inhibitors arrest the cell cycle in G1-phase. They are approved to treat breast cancer and are also undergoing clinical trials against a range of other tumour types. To facilitate these efforts, it is important to understand why a temporary cell cycle arrest in G1 causes long-lasting effects on tumour growth. Here we demonstrate that a prolonged G1-arrest following CDK4/6 inhibition downregulates replisome components and impairs origin licencing. This causes a failure in DNA replication after release fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 91 publications
(110 reference statements)
11
41
0
Order By: Relevance
“…The Saurin and Demaria groups set out with differing initial goals: Crozier et al (2022) focussed on identifying the mechanisms by which treatment with Cdk4/6 inhibitors (Cdk4/6i) promoted entry into senescence, while Wang et al (2022) aimed to characterise the downstream impact of senescence induction by Cdk4/6i. Both laboratories found that treating non‐cancer cells for a prolonged period of time (i.e.…”
Section: Figure Long‐term Cdk4/6i Treatment Causes Cells To Enter Int...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Saurin and Demaria groups set out with differing initial goals: Crozier et al (2022) focussed on identifying the mechanisms by which treatment with Cdk4/6 inhibitors (Cdk4/6i) promoted entry into senescence, while Wang et al (2022) aimed to characterise the downstream impact of senescence induction by Cdk4/6i. Both laboratories found that treating non‐cancer cells for a prolonged period of time (i.e.…”
Section: Figure Long‐term Cdk4/6i Treatment Causes Cells To Enter Int...mentioning
confidence: 99%
“…Knocking out p53 allowed cells to re‐enter the cell cycle after Cdk4/6i removal. Using live single‐cell imaging, the Saurin laboratory showed that in the presence of p53, cells after Cdk4/6i washout either remain in G0/G1 or re‐enter S‐phase, complete DNA replication and arrest in the subsequent G2, where they withdraw from the cell cycle (Crozier et al, 2022). In either phase, arrest requires p53.…”
Section: Figure Long‐term Cdk4/6i Treatment Causes Cells To Enter Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of DNA content by Hoechst sum intensity allows the gating of cells into G1, S and G2/M phases (electronic supplementary material, figure S2b) [15]. P-Rb is bimodally distributed in a population of asynchronously cycling cells, reflecting the proliferation status of the population with G0 cells (and palbociclib-arrested cells) displaying hypophosphorylated Rb [52][53][54] (electronic supplementary material, figure S2c).…”
Section: P21 and P27 Are Not Required For Entry Into G1 Arrest With Palbociclib In Rpe1 Cellsmentioning
confidence: 99%
“…When transcribed, these two viral proteins deregulate the cell cycle and impede genomic stability in the host cell by rendering several putative tumor suppressors inactive, including tumor protein 53 (p53) and retinoblastoma (Rb) (6,7). In addition, activation of cyclin-dependent kinase (CDK)-4 and -6 induces replication stress in the cervical epithelium and promotes mitotic entry despite DNA damage (6,(8)(9)(10)(11)(12). The p16 CDK inhibitor 2A (CDKN2A) protein is a principal cyclin-dependent kinase inhibitor that decelerates the cell cycle and regulates the DNA damage response (8).…”
Section: Introductionmentioning
confidence: 99%